The Effect of Talk, Touch, and Combination of both Talk and Touch Stimulation on Movement and Fetal Heart Rate among Mother with High-Risk Pregnancy - Siti Rochanah; Idriani Idriani; Suhendar Sulaeman (International Journal of Nursing and Health Services (IJNHS), 2020)
High rates of high-risk pregnancies, neonatal deaths and developmental disorders are health problems that must be prevented. Special stimulation and touch fetal stimulation is a natural way that can be done to prevent death and prevent fetal development. This action secretes receptors and the central nervous system to secrete endorphins and increase circulation for increased movement and heart rate for the dynamic balance of the pacemaker. The aim of the study was to prove the difference between speech stimulation, touch and combination in increasing fetal heart rate and movement. The study design was a quasi experimental pre-test and post-test with three intervention groups, namely the stimulation group of speech, touch and combination with 10 respondents in each group. The analysis was done by one way ANOVA. The results of one method showed no significant difference in effectiveness between the three types of stimulation. The conclusion of the study is that stimulation of speech, touch and combination are equally effective in increasing fetal heart rate and movement. This study discusses the stimulation of conversation, touch and combination that is carried out as an independent intervention of normal pregnant women and high risk in maintaining and improving fetal well-being.